2011
DOI: 10.1063/1.3636413
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the anomalous conductance plateau in asymmetrically biased InAs/In0.52Al0.48As quantum point contacts—A step towards a tunable all electric spin valve

Abstract: The appearance and evolution of an anomalous conductance plateau at 0.4(2e2/h) in an In0.52Al0.48As/InAs quantum point contact (QPC), in the presence of lateral spin-orbit coupling, has been studied at T = 4.2 K as a function of the potential asymmetry between the in-plane gates of the QPC. The anomalous plateau, a signature of spin polarization in the channel, appears only over an intermediate range (around 3 V) of bias asymmetry. It is quite robust, being observed over a maximum range of nearly 1 V of the sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 15 publications
2
29
0
Order By: Relevance
“…Recently, we showed that LSOC in InAs/InAlAs and GaAs/AlGaAs QPCs with in-plane side gates can be used to create a strongly spin-polarized current by purely electrical means in the absence of any applied magnetic field [7][8][9][10]. The use of a Non Equilibrium Green's Function (NEGF) approach to calculate the conductance of QPCs shows that the onset of spin polarization in devices with in-plane side gates required three ingredients: (1) an asymmetric lateral confinement, (2) a LSOC induced by lateral confining potential of the QPC, and (3) a strong electron-electron interaction [11,12].…”
mentioning
confidence: 99%
“…Recently, we showed that LSOC in InAs/InAlAs and GaAs/AlGaAs QPCs with in-plane side gates can be used to create a strongly spin-polarized current by purely electrical means in the absence of any applied magnetic field [7][8][9][10]. The use of a Non Equilibrium Green's Function (NEGF) approach to calculate the conductance of QPCs shows that the onset of spin polarization in devices with in-plane side gates required three ingredients: (1) an asymmetric lateral confinement, (2) a LSOC induced by lateral confining potential of the QPC, and (3) a strong electron-electron interaction [11,12].…”
mentioning
confidence: 99%
“…In such nanostructures, the spin filtering effect results from the interplay between the SO coupling 18,19 and the quantum confinement. Recent papers [9][10][11][12][13][14][15] have reported the experimental evidence of the spin filtering in QPCs, which manifests itself as the plateau of conductance at 0.5G 0 (G 0 = 2e 2 /h) measured in the absence of the external magnetic field. The 0.5G 0 plateau has been explained as resulting from the combination of the three effects 13,14,17 : an asymmetric lateral confinement, a lateral Rashba SO interaction, and an electron -electron interaction.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental realizations of spin filters based on QPCs, reported so far, are based on a two-dimensional electron gas (2DEG) confined in the narrow quantum well at the AlGaAs/GaAs or InAs/InAlAs interface 10,11 , in which the electrons occupy the lowest-energy state ("single occupancy"). However, recently, wider or coupled quantum wells with two populated subbands ("double occupancy") have attracted a growing interest of both experimentalists [24][25][26][27][28][29] and theoreticians [30][31][32][33][34][35] .…”
Section: Introductionmentioning
confidence: 99%
“…In the short wire limit, we calculate several e-e collision processes, which give rise to three distinct resonances in conductance as a function of the chemical potential, see dramatically stronger compared to the three-particle collisions in spin-degenerate case 2 . In addition, some of the e-e contributions, including the strongest linear in T negative term, vanish in the case of symmetric transverse confinement potential, providing a tool for a straightforward test of our theory [26][27][28] . Our results may explain the origin of a helical gap-like feature recently observed in a ballistic InAs nanowire 29 and pave the way towards allelectrical control of e-e collisions in clean quantum wires with strong SOC 30,31 .…”
mentioning
confidence: 96%